Experimental in vivo and in vitro treatment with a new histone deacetylase inhibitor belinostat inhibits the growth of pancreatic cancer - Dovzhanskiy, Dmitriy I.; Arnold, Stefanie M.; Hackert, Thilo; Oehme, Ina; Witt, Olaf; Felix, Klaus M.; Giese, Nathalia; Werner, Jens (BMC cancer, 2012)
Background: Treatment options for pancreatic ductal adenocarcinoma (PDAC) are limited. Histone deacetylase inhibitors are a new and promising drug family with strong anticancer activity. The aim of this study was to examine the efficacy of in vitro and in vivo treatment with the novel pan-HDAC inhibitor belinostat on the growth of human PDAC cells. Methods: The proliferation of tumour cell lines (T3M4, AsPC-1 and Panc-1) was determined using an MTT assay. Apoptosis was analysed using flow cytometry. Furthermore, p21Cip1/Waf1 and acetylated histone H4 (acH4) expression were confirmed by immunoblot analysis. The in vivo effect of belinostat was studied in a chimeric mouse model. Antitumoural activity was assessed by immunohistochemistry for Ki-67. Results: Treatment with belinostat resulted in significant in vitro and in vivo growth inhibition of PDAC cells. This was associated with a dose-dependent induction of tumour cell apoptosis. The apoptotic effect of gemcitabine was further enhanced by belinostat. Moreover, treatment with belinostat increased expression of the cell cycle regulator p21Cip1/Waf1 in Panc-1, and of acH4 in all cell lines tested. The reductions in xenograft tumour volumes were associated with inhibition of cell proliferation. Conclusion: Experimental treatment of human PDAC cells with belinostat is effective in vitro and in vivo and may enhance the efficacy of gemcitabine. A consecutive study of belinostat in pancreatic cancer patients alone, and in combination with gemcitabine, could further clarify these effects in the clinical setting.